Analysis of current protection in distribution networks with clean energy access - Kun, Huang; Rong, Cai; Jingtao, Zhao; Xundong, Gong; Guodong, Huang (Frontiers in Energy Research, 2023)
With the rapid development of the new energy industry, distributed generation (DG) is connected to the power grid on a large scale, and the traditional relay protection scheme is no longer suitable for modern power systems. In order to solve this problem, this paper establishes a mathematical model of the equivalent circuit of distributed photovoltaic power supply according to the external characteristics of photovoltaic cells, and analyzes its volt-ampmeter characteristics and voltage output characteristics of power supply. On this basis, it analyzes and puts forward the control mode of DG when the distribution network is faulty. On the basis of the study, this article has double feeder distribution network as an example, the analysis when the line fault occurring at different extents of DG connected to different position on the influence of the distribution network current protection, the results show that when answering DG side in the feeder bus for distribution network of current protection, pick a smaller effect on both ends of feeder, has a certain symmetry. Finally, the accuracy of theoretical analysis is verified by establishing a simulation model in PSCAD.